Cloud Computing as an Elucidation to Geographical Information Systems (GIS): Methodologies, Services, Opportunities, Challenges and Deployment Techniques - Rati Shukla (International Journal of Advanced Science and Technology, 2020)
Geospatial or Geographical Information Systems (GIS) known as a puddle of equipment amalgamating hardware, software, data, statistical analysis and cartography to capture, manage, analyse, store, and present data linked to geographical locations. GIS is used commonly to make possible preeminent decisions in the course of spatial in addition to non-spatial data associations, processing and visualization. Caused by the expansion of industries and large technological rise in twenty first century, geospatial sciences face striking IT challenges viz spatiotemporal, computing, data and concurrent access intensity. With the aim of providing wide-ranging spectrum facilities to the users all around the world, hard work are also being done to improve the conformist GIS applications, over a few decades. The raise of cloud computing gives a latent solution to GIS problem of large sized data requiring huge storage with an flexible, on-demand computing stage to amalgamate inspection systems, parameter extracting algorithms, analytical visualization, decision support, phenomena simulations, and to endow with social importance and user response which are vital fundamentals of the geospatial sciences. In continuation to swot the significance of cloud computing on traditional desktop GIS, it is necessary to find out what the cloud can offer and then look into some of the alternatives that are becoming obtainable today. Through comprehensive literature review and application practice, this article provides a complete understanding of opportunities and challenges of Cloud Computing approach to GIS in areas like Social Media, Geospatial Information, Emergency management, Spatial web portal. In this paper further investigated the issues, methodologies, deployed techniques and services.